In vitro Models of Neurodegenerative Diseases - Slanzi, Anna; Iannoto, Giulia; Rossi, Barbara; Zenaro, Elena; Constantin, Gabriela (Frontiers in Cell and Developmental Biology, 2020)
Neurodegenerative diseases are progressive degenerative conditions characterized by the functional deterioration and ultimate loss of neurons. These incurable and debilitating diseases affect millions of people worldwide, and therefore represent a major global health challenge with severe implications for individuals and society. Recently, several neuroprotective drugs have failed in human clinical trials despite promising pre-clinical data, suggesting that conventional cell cultures and animal models cannot precisely replicate human pathophysiology. To bridge the gap between animal and human studies, three-dimensional cell culture models have been developed from human or animal cells, allowing the effects of new therapies to be predicted more accurately by closely replicating some aspects of the brain environment, mimicking neuronal and glial cell interactions, and incorporating the effects of blood flow. In this review, we discuss the relative merits of different cerebral models, from traditional cell cultures to the latest high-throughput three-dimensional systems. We discuss their advantages and disadvantages as well as their potential to investigate the complex mechanisms of human neurodegenerative diseases. We focus on in vitro models of the most frequent age-related neurodegenerative disorders, such as Parkinson’s disease, Alzheimer’s disease and prion disease, and on multiple sclerosis, a chronic inflammatory neurodegenerative disease affecting young adults.